Choice behaviour of housing attributes: theory and measurement - Zinas, Bako Zachariah (Faculty of Architecture, Planning & Surveying, UiTM Malaysia, 2010)
Preferences and choices in a society are constant dynamic operations, made based on the behavioural dynamism of people. In this cosmic dynamism, they keep shifting from one stage to another, within the same cosmic space. Housing preferences and choices, like any other life interests, therefore operate within this framework. Unlike merchandized products brands, housing brands are hardly known, probably because of the heterogeneous nature of the housing product - the house. However, very little is known about the relevant housing attributes (refer to page 7). Housing preferences and choices operate within the framework of preferences and choices for housing attributes. In any preference and choice activity, there are underlying motivations that make it possible for an individual to choose from available alternatives within a given product field. This paper examines and outlines the methodological and theoretical framework of housing preferences and choices, based on the theory of means-end chain (MEC). Previous MEC applications in the field of architecture and urban design have been very useful and successful. The paper attempts to explore from literature the possibility of extending the previous methods and their applicability in design process. In dealing with user preference for housing, there is a need for research for a development of a technological tool to identify user needs and preference, and the kind of decision support that is required to identify these needs.